Trypanosoma cruzi isolated from a triatomine found in one of the biggest metropolitan areas of Latin America - Ribeiro, Aline Rimoldi; Oliveira, Rosane Correa de; Ceretti Junior, Walter; Lima, Luciana; Almeida, Larissa Aguiar de [UNESP]; Nascimento, Juliana Damieli; Geraldes Teixeira, Marta Maria; Rosa, Joao Aristeu da [UNESP] (Soc Brasileira Medicina Tropical, 2016)
Introduction: To characterize Trypanosoma cruzi (TcI) isolated from a Panstrongylus megistus specimen found in one of the biggest metropolitan areas of Latin America, the relationship between the TcI group of T. cruzi and the transmission cycle in the urban environment was studied. Methods: The T. cruzi strain, Pm, was isolated in a culture medium from the evolutionary forms present in the hindgut of a live male specimen of P. megistus found in the Jabaquara subway in Sao Paulo City. The sample from the triatomine showed trypomastigote forms of Trypanosomatidae, which were inoculated in the peritoneum of Balb/c mice. The sample was then inoculated in Liver Infusion Tryptose medium and J774 cells for the molecular identification and characterization of the parasite. The Pm strain of T. cruzi was identified by isolation in axenic culture medium, and based on the morphology, cell infection, growth kinetics, and molecular characterization. Results: After isolation, the protozoan was identified as T. cruzi. No parasites were detected in the peripheral blood of the animal, which can be a characteristic inherent to the strain of T. cruzi that was isolated. Cell invasion assays were performed in triplicate in the J774 cell line to confirm the invasive ability of the Pm strain and revealed amastigote forms of the parasite within macrophages. Conclusions: Our biological and molecular characterizations helped understand parasite-host interactions and their evolutionary history in context of the associations between vectors, ecotopes, hosts, and groups of the parasite.
Keywords: Trypanosoma cruzi; Panstrongylus megistus; Molecular characterization; Chagas disease